Genetic polymorphism of the methotrexate transporter ABCG2, blood pressure and markers of arterial function in patients with rheumatoid arthritis: repeated cross-sectional study - Baghdadi LR; Woodman RJ; Shanahan EM; Wiese MD; Mangoni AA (Dove Medical Press, 2018)
Leena R Baghdadi,1 Richard J Woodman,2 E Michael Shanahan,3 Michael D Wiese,4 Arduino A Mangoni5 1Department of Family and Community Medicine, College of Medicine, King Saud University and King Khalid University Hospital, Riyadh, Saudi Arabia; 2Centre for Epidemiology and Biostatistics, College of Medicine and Public Health, Flinders University, Adelaide, SA, Australia; 3Department of Rheumatology, College of Medicine and Public Health, Flinders University and Southern Adelaide Local Health Network, Adelaide, SA, Australia; 4School of Pharmacy and Medical Sciences and Sansom Institute for Health Research, University of South Australia, Adelaide, SA, Australia; 5Department of Clinical Pharmacology, College of Medicine and Public Health, Flinders University and Flinders Medical Centre, Adelaide, SA, Australia Purpose: Methotrexate (MTX) treatment is associated with lower blood pressure (BP) and arterial stiffness in rheumatoid arthritis (RA). We investigated associations between single-nucleotide polymorphism (SNP) of the ATP-binding cassette efflux transporter gene ABCG2 (rs2231142), BP, and arterial stiffness in RA patients treated with MTX. Patients and methods: Clinical and 24-hour peripheral and central BP, arterial wave reflection (Augmentation Index, AIx), arterial stiffness (Pulse Wave Velocity, PWV), and intracellular MTX polyglutamate (MTXPGs) concentrations were assessed in 56 RA patients on stable treatment with MTX using a repeated cross-sectional study design with measurements at baseline and after 8 months. Results: Majority of the RA patients were homozygotes for the normal allele (CC, n=46) whereas 10 were rs2231142 heterozygotes (AC, n=10). MTXPGs concentrations were non-significantly higher in AC when compared to CC (144.3 vs 116.3 nmol/L packed RBCs, P=0.10). At baseline, the AC group had significantly lower age-adjusted clinical systolic BP (SBP) (P=0.01), 24-hour peripheral SBP (P=0.003), and central SBP (P=0.02) when compared to the CC group. However, AIx and PWV values were not significantly different between the two groups. When data from both visits were combined in a single analysis, and additionally adjusted for visit, gender, body mass index, and Disease Activity Score 28, the trend in SBP differences between-groups persisted but was no longer significant. Conclusion: Future studies are required to test the hypothesis that this genetic polymorphism is associated with lower BP, arterial stiffness, and possibly, cardiovascular risk, in RA patients treated with MTX. Keywords: methotrexate, disease-modifying antirheumatic drugs, blood pressure, augmentation index, rheumatoid arthritis, pulse wave velocity, single-nucleotide polymorphisms, ATP-binding cassette transporters, ABCG2